Effects of Different Loading Programs on Finger Strength in Rock Climbers - Natalie K. Gilmore; Peter Klimek; Emil Abrahamsson; Keith Baar (Sports Medicine - Open)
Abstract Background Climbing places high loads through the hands and fingers, and climbers may benefit from specific finger strength training (hangboarding) protocols. The purpose of this study was to evaluate the effect of a 10-minute low intensity hangboard finger strengthening protocol (“Abrahangs”), compared with the generally accepted Max Hangs protocol for training maximal grip strength. Methods We retrospectively evaluated the change in grip strength and Strength: Weight following Max Hangs, Abrahangs, or the two protocols performed concurrently in rock climbers who used the Crimpd app to log their training. Users who had completed two finger strength tests within a 4–16-week period were included. Climbers were grouped by the number of training sessions into: “Climbing Only”, “Abrahangs Only”, “Max Hangs Only” and “Both” Max Hangs and Abrahangs. Results Frequent low intensity finger loading was as effective at improving grip strength in climbers as training with maximal loads. Additionally, combining low intensity and maximal load training resulted in additive strength gains. Conclusions These results suggest that low-intensity long duration holds provide a promising training paradigm for training finger strength that is gentle enough to incorporate into existing training programs.